Investigation of Q-switched and mode-locked erbium-doped fiber laser using graphene oxide-saturable absorber - Hamida, Belal Ahmed; Eltaif, Tawfig; Omer, Mahamat; Khan, Sheroz (Institute of Electrical and Electronics Engineers Inc., 2020)
This paper experimentally investigates a simple configuration of an erbium-doped fiber laser (EDFL) cavity to generate mode-locked and Q-switched pulses utilize graphene oxide as saturable absorber (GO-SA). The GO-SA chip is a chip placed as a sandwich between two fiber ferrules and incorporates a ring laser cavity to generate a pulse train. Results indicate that the cavity of passive Q-switching EDFL is capable of providing pulses at 1532nm with a pulse width within a range of 5.32μs to 2.6μs, a repetition rate of 59.5kHz to 71.74kHz, a pulse energy of 364.64nJ to 668.95nJ, and an output power ranging from 0.062mW to 0.136mW, when the configuration is pumped by a 980nm laser diode, the power of which gradually increases from 21.7mW to 47.9mW. The output of the GO-SA needs to be connected to 200m of a single-mode fiber (SMF) to generate mode-locked pulses at 1559nm when the pump power is 157.6mW. As a result, an output power of 1.29mW is delivered with a repetition rate of 1.002MHz.